Asparagine: A key metabolic junction in targeted tumor therapy - Xuan Wang; Weijian Gong; Xueyou Xiong; Xuemei Jia; Juan Xu (Elsevier, 2024)
Nutrient bioavailability in the tumor microenvironment plays a pivotal role in tumor proliferation and metastasis. Among these nutrients, glutamine is a key substance that promotes tumor growth and proliferation, and its downstream metabolite asparagine is also crucial in tumors. Studies have shown that when glutamine is exhausted, tumor cells can rely on asparagine to sustain their growth. Given the reliance of tumor cell proliferation on asparagine, restricting its bioavailability has emerged as promising strategy in cancer treatment. For instance, the use of asparaginase, an enzyme that depletes asparagine, has been one of the key chemotherapies for acute lymphoblastic leukemia (ALL). However, tumor cells can adapt to asparagine restriction, leading to reduced chemotherapy efficacy, and the mechanisms by which different genetically altered tumors are sensitized or adapted to asparagine restriction vary. We review the sources of asparagine and explore how limiting its bioavailability impacts the progression of specific genetically altered tumors. It is hoped that by targeting the signaling pathways involved in tumor adaptation to asparagine restriction and certain factors within these pathways, the issue of drug resistance can be addressed. Importantly, these strategies offer precise therapeutic approaches for genetically altered cancers.